Acceptance of Anxiety through Art Therapy: A Case Report Exploring How Anthroposophic Art Therapy Addresses Emotion Regulation and Executive Functioning. (28th December 2019) - Abbing, A. C.; Baars, E. W.; Van Haastrecht, O.; Ponstein, A. S.
Abstract : Anxiety is a major problem for many individuals, causing impairment in daily life. Art therapy is often deployed and although positive results are communicated in clinical practice, its effectiveness and working mechanisms have hardly been studied. Therefore, it is important to systematically describe the intervention process and to detect the working mechanisms to be able to evaluate them. Narrative case studies help to understand the intervention in more depth. A typical case file was selected for case reporting according to scientific (CARE & CARE-AAT) guidelines, with the aim to explore the therapeutic elements that contributed to the reduction of anxiety. The report describes the intervention process of a 54-year-old female, suffering from anxiety since childhood and diagnosed with panic disorder, agoraphobia, claustrophobia and hypochondria. After 14 sessions of anthroposophic art therapy, reduction of anxiety was shown, as well as improvements of emotion regulation and executive functioning. The client indicated that she became more tolerant and accepting towards her anxiety. She noted a softened attitude towards herself and her complaints, even one year after art therapy. The course of treatment suggests that aspects of emotion regulation and executive functioning were addressed through implicit learning processes in different art therapy assignments.